Gestión de la Seguridad de Información y Estrategia Tecnológica en las Consultorías de Proyectos Industriales de la Ciudad de Barranquilla (2021)
With the advancement of society, technology has gained ground and today we say that the industry must go hand in hand with it, but achieving it is a challenge, therefore, the basic aspects of Industry 4.0 have taken the technological reins of the world, a megatrend; In order to manage information and protect such a long-awaited business asset, it has globally increased activities by connecting them to all existing networks, creating a range of events updating industrial processes. That is where the technological strategies focused on the search for optimal and lasting results were born, locked in a cycle of continuous improvement allowing new technologies to automate processes without leaving human beings aside. Its challenge is to analyze the management of information security and its technological strategy developed in the consultancies of industrial projects of the city of Barranquilla.